Walt Disney, young movie maker - Hammontree, Marie; Irvin, Fred M. (New York : Aladdin Paperbacks, 1997)
A biography concentrating on the boyhood of the cartoonist and film maker who created Mickey Mouse and Donald Duck
Originally published: Indianapolis : Bobbs-Merrill, 1969, in series: Childhood of famous Americans series
Keywords: Disney, Walt, -- 1901-1966 -- Childhood and youth; Disney, Walt, -- 1901-1966 -- Juvenile literature; Animators -- United States -- Biography -- Juvenile literature; Motion picture producers and directors -- United States -- Biography -- Juvenile literature; Motion pictures -- Biography